Voices of resistance: intersectionality and agency in Maya Angelou's I know why the caged bird sings - Francisco, Dayane Evellin de Souza (2016)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2016.